The Relationship between the Health Belief Model and COVID-19 Preventive Behaviors among Junior High School Students during the Endemic Phase in Mueang District, Surat Thani Province - Rueangsawat, Sarawut; Teepapal, Thanida (Journal of The Royal Thai Army Nurses, 2025)
This research aimed to study 1) health belief model and self-care behaviors for COVID-19 prevention, 2) the relationship between health belief model and self-care behaviors for COVID-19 prevention during the endemic phase. The sample consisted of 450 junior high school students in Mueang District, Surat Thani Province. The research instruments were questionnaires on health beliefs and self-care behaviors, with reliability coefficients of 0.89 and 0.94, respectively. Data were analyzed using descriptive statistics and Pearson’s correlation coefficient. The research findings revealed that 1) health belief model regarding COVID-19 were at high levels in almost all aspects, except for perceived barriers which were at a moderate level, and self-care health behaviors in both phases were at high levels; 2) health belief model had moderate positive correlations with self-care health behaviors in both phases (p<.01). Recommendations: Adapting health education programs in schools adjustments should focus on changing health beliefs, particularly risk perception and disease severity, and continuously promote correct health beliefs even during the endemic phase.